Analysis Of Violations Construction Of Buildings In Normative Law - Melki Suheri Simamora (Universitas Dharmawangsa, 2023)
Spatial planning is one of the challenges faced by the government City due to violations of the construction of buildings by the community that not only harm the surrounding community but also disrupt the spatial order that has been planned by the city government. This study discusses several law enforcement regulations violation of the construction of buildings in the city of Semarang by using the method empirical juridical research and statute approach method conducted by reviewing legislation and interviews with the Department related to the purpose that people understand urban planning and the consequences if breaking.